2011
DOI: 10.1021/es200022q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Transgenic Insecticidal Cry1Ab Protein to Silica Particles. Effects on Transport and Bioactivity

Abstract: Bt crops are genetically modified to be resistant against insect pests by expressing insecticidal Cry proteins. The processes governing the fate and bioavailability of the expressed transgenic Cry proteins in soils are poorly understood. We studied adsorption of Cry1Ab to negatively charged silica (SiO(2)) particles, a major soil constituent and a model for negatively charged mineral surfaces, at pH 5 to 10 and ionic strengths I = 10 mM to 250 mM, both in solution depletion and saturated column transport exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 22 publications
5
44
1
Order By: Relevance
“…This profile of decreased detectability of toxins is congruent with previous studies which investigated the fate of soluble Cry3 and Cry1 toxins in different soils (1,19,21,30). It seems that the heterogeneous structure of the leaf litters is close to the structure of soils, generating the same toxin adsorption profiles (25). In the present work, we used toxins in their crystal form instead of soluble toxins, and we obtained similar results.…”
Section: Discussionsupporting
confidence: 90%
“…This profile of decreased detectability of toxins is congruent with previous studies which investigated the fate of soluble Cry3 and Cry1 toxins in different soils (1,19,21,30). It seems that the heterogeneous structure of the leaf litters is close to the structure of soils, generating the same toxin adsorption profiles (25). In the present work, we used toxins in their crystal form instead of soluble toxins, and we obtained similar results.…”
Section: Discussionsupporting
confidence: 90%
“…29 Such congruence between more traditional techniques and QCM-D and OWLS was recently highlighted in a study examining adsorption of transgenic insecticidal crystal (Cry) proteins derived from Bacillus thuringiensis to SiO 2 . 60 The areal surface densities for pathogenic PrP attaching to SiO 2 in the present study were lower than those previously reported by Johnson et al 27 This discrepancy is likely due primarily to limitations in the detection method applied in the earlier study. We find that solution chemistry strongly impacts prion attachment to SiO 2 surfaces.…”
Section: Resultscontrasting
confidence: 79%
“…It has been shown that Cry toxins bound to the soil (37) or to leaf litter (present study) conserve their entire antigenicity and insecticidal activity. However, Cyt toxins have very different 3D conformations than Cry toxins and may interact differently with the heterogenic sorbent surface of the leaf litter, explaining why they partly lose their immunological detectability and synergistic effects (26). Even if the toxin extraction protocol coupled with ELISAs showed good efficiency and reproducibility for all toxins (see Fig.…”
Section: Discussionmentioning
confidence: 99%